Rancang Bangun Sistem Informasi Administrasi Layanan Pasien Berbasis Web Pada Klinik Paradise Surabaya - Malina Amaliyah; Haryanto Tanuwijaya; Tutut Wurijanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Clinic Paradise Surabaya is a medical services have full facilities and experts in the form of general practitioner, beauty, dentist, pharmacy, laboratory, and beauty care services. Obstacles faced Clinic Paradise Surabaya is in the administration of patient services ranging from patient registration, queues, record-keeping, drug and redemption payments are still written or recorded on a sheet of paper. To overcome the above problems, it is made Design of Information System Administration Patient Services Web Based in Clinic Paradise Surabaya processing registration examination, the queue of patients, recording medical records, prescription drugs redemption, payment and reporting required owner. Web-based applications that can run on any operating system and can be accessed through many media such as computers, tablets, and smartphones. Conclusion of Information System Administration Patient Services Web Based is able to help the registration process checks for patients who are already registered, new patient registration, automatic numbering for each poly queues, record-keeping, drug redemption, and payment. Generate reports of patient visit, new patient registration statements, reports of medical records of patients, most diseases reports, income statements, and reports of drug expenditures.Keywords : Information System, Administration Patient Service, Medical Record, Clinic.